AGL15, a MADS domain protein expressed in developing embryos. - Heck, G R (1995)
To extend our knowledge of genes expressed during early embryogenesis, the differential display technique was used to identify and isolate mRNA sequences that accumulate preferentially in young Brassica napus embryos. One of these genes encodes a new member of the MADS domain family of regulatory proteins; it has been designated AGL15 (for AGAMOUS-like). AGL15 shows a novel pattern of expression that is distinct from those of previously characterized family members. RNA gel blot analyses and in situ hybridization techniques were used to demonstrate that AGL15 mRNA accumulated primarily in the embryo and was present in all embryonic tissues, beginning at least as early as late globular stage in B. napus. Genomic and cDNA clones corresponding to two AGL15 genes from B. napus and the homologous single-copy gene from Arabidopsis, which is located on chromosome 5, were isolated and analyzed. Antibodies prepared against overexpressed Brassica AGL15 lacking the conserved MADS domain were used to probe immunoblots, and AGL15-related proteins were found in embryos of a variety of angiosperms, including plants as distantly related as maize. Based on these data, we suggest that AGL15 is likely to be an important component of the regulatory circuitry directing seed-specific processes in the developing embryo.